Synchronization of repolarization after cardiac resynchronization therapy: A combined clinical and modeling study. (11th June 2022) - Verzaal, Nienke J.; van Deursen, Caroline J. M.; Pezzuto, Simone; Wecke, Liliane; van Everdingen, Wouter M.; Vernooy, Kevin; Delhaas, Tammo; Auricchio, Angelo; Prinzen, Frits W.
Abstract: Introduction: The changes in ventricular repolarization after cardiac resynchronization therapy (CRT) are poorly understood. This knowledge gap is addressed using a multimodality approach including electrocardiographic and echocardiographic measurements in patients and using patient‐specific computational modeling. Methods: In 33 patients electrocardiographic and echocardiographic measurements were performed before and at various intervals after CRT, both during CRT‐ON and temporary CRT‐OFF. T‐wave area was calculated from vectorcardiograms, and reconstructed from the 12‐lead electrocardiography (ECG). Computer simulations were performed using a patient‐specific eikonal model of cardiac activation with spatially varying action potential duration (APD) and repolarization rate, fit to a patient's ECG. Results: During CRT‐ON T‐wave area diminished within a day and remained stable thereafter, whereas QT‐interval did not change significantly. During CRT‐OFF T‐wave area doubled within 5 days of CRT, while QT‐interval and peak‐to‐end T‐wave interval hardly changed. Left ventricular (LV) ejection fraction only increased significantly increased after 1 month of CRT. Computer simulations indicated that the increase in T‐wave area during CRT‐OFF can be explained by changes in APD following chronic CRT that are opposite to the change in CRT‐induced activation time. These APD changes were associated with a reduction in LV dispersion in repolarization during chronic CRT. Conclusion: T‐wave area during CRT‐OFF is a sensitive marker for adaptations in ventricular repolarization during chronic CRT that may include a reduction in LV dispersion of repolarization. Abstract : Personalized in silico model showed that T‐wave area during CRT‐OFF is a sensitive marker for adaptations in ventricular repolarization after CRT.